2020
DOI: 10.4049/jimmunol.204.supp.67.11
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Study of Daily Cannabidiol for the Treatment of Canine Osteoarthritis

Abstract: Hemp-derived cannabidiol (CBD) is the major non-psychoactive component of cannabis and has been promoted as a potential treatment for a wide variety of disparate inflammatory conditions. Here we evaluated CBD for its ability to modulate the production of pro-inflammatory cytokines in vitro and in murine models of induced inflammation and further validated the ability of a liposomal formulation to increase bioavailability in mice and in humans. Subsequently, the therapeutic potential of both naked and liposomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…While the only current FDA-approved use for CBD is as an anticonvulsant to treat seizures associated with Lennox-Gastaut syndrome, Dravet syndrome, or tuberous sclerosis complex ( 17 ), recent studies have indicated additional therapeutic benefits of CBD including anti-inflammatory ( 18 ), antioxidant ( 19 , 20 ), analgesic ( 21 ), antiemetic ( 22 ), anxiolytic ( 23 ), anticarcinogenic ( 24 , 25 ), antimicrobial ( 26 , 27 ), and immunomodulatory ( 21 , 28 ) properties. More specifically, research in various species has evaluated its efficacy in treating diseases such as diabetes mellitus ( 29–31 ), osteoarthritis ( 21 , 28 , 32 ), and neurologic diseases (e.g., Alzheimer’s, Parkinson’s) ( 33–37 ). In addition, CBD has been proposed to treat symptoms associated with stress ( 38 ), gastrointestinal disturbances ( 39 , 40 ), orofacial pain ( 41 , 42 ), hypertension ( 43–45 ), and neoplastic processes ( 46 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the only current FDA-approved use for CBD is as an anticonvulsant to treat seizures associated with Lennox-Gastaut syndrome, Dravet syndrome, or tuberous sclerosis complex ( 17 ), recent studies have indicated additional therapeutic benefits of CBD including anti-inflammatory ( 18 ), antioxidant ( 19 , 20 ), analgesic ( 21 ), antiemetic ( 22 ), anxiolytic ( 23 ), anticarcinogenic ( 24 , 25 ), antimicrobial ( 26 , 27 ), and immunomodulatory ( 21 , 28 ) properties. More specifically, research in various species has evaluated its efficacy in treating diseases such as diabetes mellitus ( 29–31 ), osteoarthritis ( 21 , 28 , 32 ), and neurologic diseases (e.g., Alzheimer’s, Parkinson’s) ( 33–37 ). In addition, CBD has been proposed to treat symptoms associated with stress ( 38 ), gastrointestinal disturbances ( 39 , 40 ), orofacial pain ( 41 , 42 ), hypertension ( 43–45 ), and neoplastic processes ( 46 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are no current studies published about the use of CBD or CBDA as a potential therapeutic agent in nonhuman primates (NHP); however, oral high-dose CBD (30–300 mg/kg) for 90 days ( n = 16) did not affect rhesus macaque growth rates but increased liver and kidney weights, decreased testicular weight and inhibited spermatogenesis, dose-dependently decreased red blood cell counts, and occasionally resulted in transient diarrhea ( 66 ). Based on evidence of the therapeutic benefits in humans and other species ( 32 , 38 , 40 ), low-dose CBD could be a candidate as an adjunctive therapy for some common NHP medical conditions, including osteoarthritis ( 67 ), environmental stress ( 68 ), and inflammatory diarrheal disease ( 69 ). As a first step, a pharmacokinetic (PK) analysis of CBD and CBDA would inform whether doses recently reported in other species would be appropriate in macaques and provide a baseline for future studies evaluating its PK or therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%